INTERFERENSI MORFOLOGIS PENUTUR BAHASA OGAN DALAM BERBAHASA INDONESIA (Sebuah Tinjauan Sosiolinguistik) - Anam, Samsul; Lestari, Dewi; Darningwati, Darningwati (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This research entitled “Morphology Interference By Ogan User In Using Indonesia Language” discuss about errors that doing by Ogan user in using Indonesia. Analysis result show that error volume that happen in user Ogan area when using Indonesian language is so intens, both phonology field and morphology. The erros that happen in phonology field like substitution and losing phonem and in morphology field like using regency words and the error in contrukstion word. Caused factors of errors that doing by Ogan user in using Indonesia are usually factor, age factor, education factor, balancing factor, and culture factor.